1 12 + 1 13 = 1 · 13 12 · 13 + 1 · 12 13 · 12 = 13 156 + 12 156 = 13 + 12 156 = 25 156 ≈ 0.160
1 12 - 1 13 = 1·13 12·13 - 1·12 13·12 = 13 156 - 12 156 = 13 - 12 156 = 1 156 ≈ 0.006
( 1 10 )3 = 1 1000
( 25 156 )2 = 625 24336
( 1 156 )2 = 1 24336
625 24336 ÷ 1 24336 = 625 24336 × 24336 1 = 625·24336 24336·1 = 15210000 24336 = 625 · 24336 24336 = 625 = 625
625× 1 1000 = 625·1 1000 = 625 1000 = 5 · 125 8 · 125 = 5 8 = 0.625
1) -96
2) -450
3) 2.28
4) 0.25
5) -2.05
6) 10,58
7) 127
8) 18
9) 7-4m
10) +5 and -5
11) x-16
12) 30